2021
DOI: 10.1007/s10518-021-01265-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of site effects on elevated seismic demands and corollary structural damage during the October 30, 2020, M7.0 Samos Island (Aegean Sea) Earthquake

Abstract: On October 30, 2020 14:51 (UTC), a moment magnitude (M) 7.0 (USGS, EMSC) earthquake occurred in the Aegean Sea. This paper presents the reconnaissance findings regarding the site effects on recorded strong ground motion intensities and duration, along with the resulting induced-structural damage in Izmir Bay and Samos Island, respectively. In all rock records, relatively high intensity long period rock spectral accelerations were observed in the mid to long period range of 0.5-1.5 s, which are attributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Discussions presented in this paper will focus on the documentation and the preliminary assessment of (i) performance of building foundations, (ii) seismic soil liquefaction and induced ground failures, (iii) performance of slopes and deep excavations, and (iv) performance of retaining structures and quay walls on both Samos and the Anatolian side for each case. As will be notable throughout the paper, with the exception of the Bayrakli region where significant and detrimental site effects (as discussed by Cetin et al 2021) were observed, no major geotechnical effects were observed on the Anatolian side in the form of foundation failures, surface manifestation of liquefaction and lateral soil spreading, rock falls/landslides, failures of deep excavations, retaining structures, quay walls and subway tunnels.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Discussions presented in this paper will focus on the documentation and the preliminary assessment of (i) performance of building foundations, (ii) seismic soil liquefaction and induced ground failures, (iii) performance of slopes and deep excavations, and (iv) performance of retaining structures and quay walls on both Samos and the Anatolian side for each case. As will be notable throughout the paper, with the exception of the Bayrakli region where significant and detrimental site effects (as discussed by Cetin et al 2021) were observed, no major geotechnical effects were observed on the Anatolian side in the form of foundation failures, surface manifestation of liquefaction and lateral soil spreading, rock falls/landslides, failures of deep excavations, retaining structures, quay walls and subway tunnels.…”
Section: Introductionmentioning
confidence: 83%
“…Nevertheless, the associated phenomena were not spectacular, which indicates that liquefaction was manifested but not in a pervasive manner. This is surprising given the intensity (PGAs > 0.2 g) and duration (≈ 9 s in records at Vathy; see Cetin et al 2021) of ground motion in combination with the nearshore alluvial deposits. The precise dimensions of the liquefied zones is hard to establish without detailed site investigations.…”
Section: Major Findings and Conclusionmentioning
confidence: 94%
See 2 more Smart Citations
“…To carry out SRA, a highly critical input parameter is the shear wave velocity (Vs) profile of the site. The Vs profile of a site is also required in studies related to geophysical characterization, site effects and many others (Ciancimino et al 2020;Cetin et al 2021;Pasten et al 2021). Presently, surface wave methods have become the most common techniques to get the Vs profile of the soil, particularly the MASW method (Park et al 1999;Xia et al 1999).…”
Section: Introductionmentioning
confidence: 99%